Direct fabrication of compositionally graded Ti-Al2O3 multi-material structures using Laser Engineered Net Shaping - Zhang, Yanning; Bandyopadhyay, Amit (Additive manufacturing, 2018)
[Display omitted] •Direct additive manufacturing of ceramics using melt cast route.•Fabrication of compositionally gradient ceramic-metal structure in one additive manufacturing operation.•Characterization and defect analysis of AM processed parts. Laser Engineered Net Shaping (LENS™), which is a laser based additive manufacturing method, was utilized to fabricate Ti-Al2O3 compositionally graded structures. The Ti-Al2O3 graded composites consisted of different sections −Ti6Al4V alloy, Ti6Al4V + Al2O3 composites, and pure Al2O3 ceramic. After LENS™ processing, microstructural characterization, phase analysis, elemental distribution, and microhardness measurements were performed on the cross sections of Ti-Al2O3 graded composites. Each section had their unique microstructures and phases. Moreover, hardness measurements demonstrated that the pure Al2O3 section had the highest hardness of 2365.5 ± 64.7 HV0.3. Conventional ceramic processing requires extensive post-processing including high temperature sintering, which makes it difficult for direct fabrication of metal-ceramic multi-layer structures. The results demonstrate that LENS™ can be utilized to process multi-material metal ceramic composites in a single step while maintaining the size, shape and compositional variations based on computer aided design files. Since this is a first-generation work, and limited research results are available in published literature related to LENS™ processing of both metals and ceramics in one operation, the demonstration of this work is expected to inspire future studies on manufacturing of multi-material composites using AM.